2003
DOI: 10.1093/jac/dkg449
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Streptococcus mutans biofilm accumulation and polysaccharide production by apigenin and tt-farnesol

Abstract: Apigenin and tt-farnesol affected the accumulation and polysaccharide content of S. mutans biofilms without major impact on the bacterial viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
340
3
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(376 citation statements)
references
References 42 publications
10
340
3
9
Order By: Relevance
“…8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionsupporting
confidence: 74%
“…10 Moreover, some flavonoids, terpenoids, isoflavones and other phenolic acids contained in propolis were found to diminish S. mutans acid production and tolerance. 10,11,12 Overall, a large number of biological activities have been attributed to different types of propolis, including antimicrobial, antifungal, antitumor, and others. 9 Propolis type 12, from southeastern Brazil, 13 demonstrated strong antibacterial effects and prevented caries development in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The water-insoluble EPS of biofilms was determined by the anthrone method [30]. Briefly, biofilms were collected by sonication/vortexing in PBS buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilms (48 h) were washed twice with 0.89% NaCl and detached by individually scratching the wells with a pipette tip and 2 mL 0.89% NaCl. Then, biofilms were separated for Log 10 (CFU/mL) determination (0.1 mL) and for total biomass determination [36] (0.1 mL). After that, biofilms were vortexed, centrifuged (5,500× g /10 min/4°C) and the supernatant containing the soluble part of the matrix was separated from the pellet, which contained the insoluble part of the matrix.…”
Section: Methodsmentioning
confidence: 99%